Impact of binaural beat stimulation on working memory: a graph theory network approach - Mujib, Muhammad Danish; Rao, Ahmad Zahid; Hasan, Muhammad Abul; Alokaily, Ahmad O.; Shaikh, Fizza Zia; Aldohbeyb, Ahmed A.; Qazi, Saad Ahmed (Frontiers in Neuroscience, 2026)
IntroductionBinaural beat (BB) stimulation has been shown to enhance working memory (WM); however, its role in information segregation and neural processing mechanisms remains insufficiently explored. This study hypothesized that improvements in WM recall are associated with enhanced θ-band–mediated information segregation in frontal brain regions.MethodsSixty healthy participants were randomly assigned to three BB stimulation groups: Group A (α-BB, 10 Hz), Group B (β-BB, 14 Hz), and Group C (γ-BB, 30 Hz). Electroencephalography (EEG; 14 channels, 128 Hz sampling rate) was recorded before (Pre), during (Du), and after (Post) BB stimulation. Cognitive performance was assessed using a digit-span test. EEG power spectra and graph-theoretical network metrics were analyzed across θ, α, β, and γ frequency bands. Correlations between EEG measures and cognitive changes were computed, and paired t-tests were used to compare Pre-, Du-, and Post-BB conditions.Resultsθ-band activity showed a significant positive correlation with cognitive improvements, particularly in frontal and parietal regions. Group A demonstrated significant increases in θ-band clustering coefficient and local efficiency at both global and fronto-parietal network levels, along with enhanced in-degree and out-degree centrality. Group C exhibited increased θ-band clustering coefficient during the Post-BB phase and greater betweenness centrality in fronto-parietal regions. No comparable effects were observed in Group B.DiscussionThe findings indicate that BB stimulation, particularly at α and γ frequencies, enhances WM performance through θ-band–mediated improvements in brain network efficiency and information segregation. These results support the potential of BB stimulation as a non-pharmacological approach for cognitive enhancement and provide insight into the neural mechanisms underlying WM modulation.